2019
DOI: 10.24903/bej.v1i1.294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Use of Video on English Vocabulary Mastery of The Elementary Second Level Students at SDN 018 Samarinda

Abstract: Vocabulary is one of language components that plays an important role in communication. Through vocabulary, students can develop the four skills in English language such as listening, reading, writing, and speaking. There are many ways in teaching vocabulary and increasing vocabulary mastery. In this study, the writer used video as a technique.   In this study, the writer wants to found out that has any significant effect of the use of Video on English vocabulary mastery of the elementary second level students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Therefore, there is no doubt that the use of technology can overcome and provide solutions to educational problems (Alwehaibi, 2015). According to Pane & Geroda (2019) using video to teach vocabulary resulted in better vocabulary mastery than previously.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no doubt that the use of technology can overcome and provide solutions to educational problems (Alwehaibi, 2015). According to Pane & Geroda (2019) using video to teach vocabulary resulted in better vocabulary mastery than previously.…”
Section: Discussionmentioning
confidence: 99%
“…Listening with excitement or interest will help the vocabulary in the lyrics stick longer in the students' head (Alipour et al, 2012). Moreover, many experimental studies have proven its effect on students' vocabulary learning (Alipour et al, 2012;Purnamasari, 2020;Roohani & Akbarpour, 2016;Tomczak & Lew, 2019). Findings have shown that using songs, despite its debate whether it is a teaching tool or 'mere' time filler, has made learning more enjoyable thus vocabulary could be learned even stuck in their mind effortlessly.…”
Section: Introductionmentioning
confidence: 99%